Binge drinking and blood pressure: cross-sectional results of the HAPIEE study. - Andrzej Pajak (Public Library of Science (PLoS), 2013)
Objectives To investigate whether binge drinking pattern influences blood pressure independently from drinking volume or whether it modifies the effect of volume of drinking. Methods We used cross-sectional data from population samples of 7559 men and 7471 women aged 45-69 years in 2002-05, not on antihypertensive medication, from Russia, Poland and Czech Republic. Annual alcohol intake, drinking frequency and binge drinking (≥ 100 g in men and ≥ 60 g in women in one session at least once a month) were estimated from graduated frequency questionnaire. Blood pressure was analysed as continuous variables (systolic and diastolic pressure) and a binary outcome (≥ 140/90 mm Hg). Results In men, annual alcohol intake and drinking frequency were strongly associated with blood pressure. The odds ratio of high blood pressure for binge drinking in men was 1.62 (95% CI 1.45-1.82) after controlling for age, country, body mass index, education and smoking; additional adjustment for annual alcohol intake reduced it to 1.20 (1.03-1.39). In women, the fully adjusted odds ratio of high blood pressure for binge drinking was 1.31 (1.05-1.63). Binge drinking did not modify the effect of annual alcohol intake. Consuming alcohol as wine, beer or spirits had similar effects. Conclusions The results suggest that the independent long-term effect of binge drinking was modest, that binge drinking did not modify the effect of alcohol intake, and that different alcoholic beverages had similar effects on blood pressure.